Singular value decomposition in an inverse source problem - Kabanikhin, S. I.; Krivorot’, O. I. (Numerical analysis and applications, 2012)
An inverse source problem for the wave equation with additional information measured on some parts of the boundary is considered. The degree of ill-posedness of the inverse problem is investigated. A numerical algorithm based on the SVD of a discrete inverse problem is constructed and tested.